Microsphere-to-nanotube transition via in situ sonication triggered in a supramolecular self-assembly system based on triphenylamine derivative. Issue 8 (3rd August 2018) - Cao, Xinhua; Gao, Aiping; Liu, Dan; Zhao, Na; Ding, Qianqian; Li, Yiran
Abstract: A new gelator1 containing triphenylamine was designed and synthesized, and formed stable gel in ethyl acetate. The self-assembly process of molecule1 was thoroughly investigated. The solid microsphere structure formed in gel1 could be turned into nanotube in the transition process of gel to gel via sonication. At the same time, the intermolecular hydrogen bond of self-assembly system was obviously enhanced under sonication. The XRD and water contact angle experiments results of xerogel1 before and after sonication showed great difference. The hydrophobicity of xerogel1 film was obviously decreased with the change of contact angle from 142° to 129° after sonication at 100 W for one minute. From the results, it was possible that the solid microsphere was re-dissolved and further reassembled into nanotube. To our knowledge, it was the first example that the solid sphere structure was changed into nanotube in self-assembly system via sonication. Abstract :